Network meta‐analysis of lorcaserin and oral hypoglycaemics for patients with type 2 diabetes mellitus and obesity. Issue 6 (10th September 2017) - Neff, L. M.; Broder, M. S.; Beenhouwer, D.; Chang, E.; Papoyan, E.; Wang, Z. W.
Summary: In addition to weight loss, randomized controlled trials have shown improvement in glycaemic control in patients taking lorcaserin. The aim of this study aim was to compare adding lorcaserin or other glucose lowering medications to metformin on weight and glycaemic control. A systematic review and network meta‐analysis of randomized controlled trials were conducted. Included studies (published 1990–2014) were of lorcaserin or glucose lowering medications in type 2 diabetic patients compared to placebo or different active treatments. Studies had to report ≥1 key outcome (change in weight or HbA1c, % HbA1c <7, hypoglycaemia). Direct meta‐analysis was performed using DerSimonian and Laird random effects models, and network meta‐analysis with Bayesian Markov‐chain Monte Carlo random effects models; 6552 articles were screened and 41 included. Lorcaserin reduced weight significantly more than thiazolidinediones, glinides, sulphonylureas and dipeptidyl peptidase‐4 inhibitors, some of which may have led to weight gain. There were no significant differences in weight change between lorcaserin and alpha‐glucoside inhibitors, glucagon‐like peptide‐1 agonists and sodium/glucose cotransporter 2 inhibitors. Network meta‐analysis showed lorcaserin was non‐inferior to all other agents on HbA1c reduction and % achieving HbA1c of <7%. The risk of hypoglycaemia was not significantly different among studied agents except that sulphonylureas were associated with higher risk of hypoglycaemia than lorcaserin. Although additional studies are needed, this analysis suggests in a population of patients with a body mas index of ≥27 who do not achieve glycaemic control on a single agent, lorcaserin may be added as an alternative to an add‐on glucose lowering medication.